2007
DOI: 10.1126/science.1137695
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Air Pollution: Origins and Impacts

Abstract: Notable warming trends have been observed in the Arctic. Although increased human-induced emissions of long-lived greenhouse gases are certainly the main driving factor, air pollutants, such as aerosols and ozone, are also important. Air pollutants are transported to the Arctic, primarily from Eurasia, leading to high concentrations in winter and spring (Arctic haze). Local ship emissions and summertime boreal forest fires may also be important pollution sources. Aerosols and ozone could be perturbing the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
465
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(495 citation statements)
references
References 50 publications
26
465
1
3
Order By: Relevance
“…While in earlier studies on Arctic Haze (Rahn, 1981;Barrie, 1986;Yamanouchi et al, 2005;Law and Stohl, 2007) an anthropogenic origin was already shown, several publications during recent years also revealed that biomass burning (as well forest fire as from agricultural origin) is one possibly important constituent of Arctic Haze as well (Warneke et al, 2009;Fu et al, 2009;Stohl et al, 2007). However, so far to our knowledge biomass burning aerosol has overwhelmingly been observed in summer over Spitsbergen or due to agricultural flaming in eastern Europe once in May 2006 .…”
Section: Introductionmentioning
confidence: 84%
“…While in earlier studies on Arctic Haze (Rahn, 1981;Barrie, 1986;Yamanouchi et al, 2005;Law and Stohl, 2007) an anthropogenic origin was already shown, several publications during recent years also revealed that biomass burning (as well forest fire as from agricultural origin) is one possibly important constituent of Arctic Haze as well (Warneke et al, 2009;Fu et al, 2009;Stohl et al, 2007). However, so far to our knowledge biomass burning aerosol has overwhelmingly been observed in summer over Spitsbergen or due to agricultural flaming in eastern Europe once in May 2006 .…”
Section: Introductionmentioning
confidence: 84%
“…Shaw, 1995;Stohl et al, 2006). Ozone and aerosols are the main short-lived species transported toward the Arctic that impact significantly the climate of this region, modifying regionally the radiative balance of the atmosphere (Law and Stohl, 2007). Ozone is a strong greenhouse gas, inducing a positive radiative forcing and causing a regional increase of the surface temperature (Shindell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these is the importance of the formation of isoprene (and isoprene oxidation product) nitrates for remote tropospheric ozone burdens. These nitrates are of a sufficient lifetime to undergo transport and hence affect concentrations some distance from emission source areas (von Kuhlmann et al, 2004;Ito et al, 2007;Law and Stohl, 2007;Young et al, 2009). They therefore have the potential to cause remote regional changes in climate but it is not known if this potential is realised.…”
Section: Biological Emission Of Reactive Carbon and Nitrogenmentioning
confidence: 99%
“…The arctic appears particularly vulnerable to aerosols (Garrett and Zhao, 2006), transported, for instance, from boreal forest fires or agricultural burning in parts of Europe and northern Asia (Generoso et al, 2007;Stohl, 2006). The deposition of black carbon on ice and snow has a large effect in terms of radiative forcing and this could accelerate regional warming and trigger important biophysical (albedo) and biogeochemical (release of soil and peat carbon) feedbacks in the climate system (Law and Stohl, 2007;Quinn et al, 2008). A second region that shows potential sensitivity to aerosols is Australia (Rotstayn et al, 2007) where increasing rainfall over northwest of the continent has been linked to Asian aerosol emissions.…”
Section: Fire and Emissions Of Chemicals And Aerosolsmentioning
confidence: 99%